Exceedingly Small Gadolinium Oxide Nanoparticles with Remarkable Relaxivities for Magnetic Resonance Imaging of Tumors. Issue 41 (25th August 2019) - Shen, Zheyu; Fan, Wenpei; Yang, Zhen; Liu, Yijing; Bregadze, Vladimir I.; Mandal, Swadhin K.; Yung, Bryant C.; Lin, Lisen; Liu, Ting; Tang, Wei; Shan, Lingling; Liu, Yuan; et al.
Abstract: Gd chelates have occupied most of the market of magnetic resonance imaging (MRI) contrast agents for decades. However, there have been some problems (nephrotoxicity, non‐specificity, and low r 1 ) that limit their applications. Herein, a wet‐chemical method is proposed for facile synthesis of poly(acrylic acid) (PAA) stabilized exceedingly small gadolinium oxide nanoparticles (ES‐GON‐PAA) with an excellent water dispersibility and a size smaller than 2.0 nm, which is a powerful T 1 ‐weighted MRI contrast agent for diagnosis of diseases due to its remarkable relaxivities ( r 1 = 70.2 ± 1.8 mM −1 s −1, and r 2 / r 1 = 1.02 ± 0.03, at 1.5 T). The r 1 is much higher and the r 2 / r 1 is lower than that of the commercial Gd chelates and reported gadolinium oxide nanoparticles (GONs). Further ES‐GON‐PAA is developed with conjugation of RGD2 (RGD dimer) (i.e., ES‐GON‐PAA@RGD2) for T 1 ‐weighted MRI of tumors that overexpress RGD receptors (i.e., integrin αv β 3 ). The maximum signal enhancement (ΔSNR) for T 1 ‐weighted MRI of tumors reaches up to 372 ± 56% at 2 h post‐injection of ES‐GON‐PAA@RGD2, which is much higher than commercial Gd‐chelates (<80%). Due to the high biocompatibility and high tumor accumulation, ES‐GON‐PAA@RGD2 with remarkable relaxivities is a promising and powerful T 1 ‐weighted MRI contrast agent. Abstract : Poly(acrylic acid) (PAA) stabilized exceedingly small gadolinium oxide nanoparticles (ES‐GON‐PAA) can be used for high contrast T 1 ‐weighted magnetic resonance imaging of tumors because of their exceedingly small particle size (<2 nm), and remarkable relaxivities ( r 1 = 70.2 ± 1.8 mM −1 s −1, and r 2 / r 1 = 1.02 ± 0.03, 1.5 T) at high PAA/Gd molar ratio.